2018
DOI: 10.3389/fpsyg.2018.00458
|View full text |Cite
|
Sign up to set email alerts
|

Tapping Into Rate Flexibility: Musical Training Facilitates Synchronization Around Spontaneous Production Rates

Abstract: The ability to flexibly adapt one’s behavior is critical for social tasks such as speech and music performance, in which individuals must coordinate the timing of their actions with others. Natural movement frequencies, also called spontaneous rates, constrain synchronization accuracy between partners during duet music performance, whereas musical training enhances synchronization accuracy. We investigated the combined influences of these factors on the flexibility with which individuals can synchronize their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
146
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(193 citation statements)
references
References 44 publications
(99 reference statements)
26
146
1
1
Order By: Relevance
“…Thus, these dynamic signatures provide evidence that the highest performing individuals are better at learning to use information from the audio cues to mirror the avatar, enabling them to perform well in regions of parameter space [21,28,29]. The enhanced stability of mirroring runs that we observe is consistent with studies showing that short training sessions reduce error rates and temporal variability in motor tasks [16]. We find that the observed dynamics have signature distributions of temporal variation that have not been explored in other experiments though studies have shown that dancers show stronger coherence when following new motions versus non-dancers over a range of time scales [28].…”
Section: Discussionsupporting
confidence: 86%
“…Thus, these dynamic signatures provide evidence that the highest performing individuals are better at learning to use information from the audio cues to mirror the avatar, enabling them to perform well in regions of parameter space [21,28,29]. The enhanced stability of mirroring runs that we observe is consistent with studies showing that short training sessions reduce error rates and temporal variability in motor tasks [16]. We find that the observed dynamics have signature distributions of temporal variation that have not been explored in other experiments though studies have shown that dancers show stronger coherence when following new motions versus non-dancers over a range of time scales [28].…”
Section: Discussionsupporting
confidence: 86%
“…For the current study, groups were matched on musical training, so this should not systematically affect our results. We are left with intrinsic rate: a more negative phase angle in the AS group should suggest a faster intrinsic rate . The current study did not examine spontaneous rates, but Subramanian and Yairi did, asking individuals who stutter to tap at a “comfortable rate” and “as fast as possible.” They found slower “comfortable” rates along with faster and more variable “fast” rates .…”
Section: Discussionmentioning
confidence: 95%
“…In the general population, mean asynchronies are often related to musical training and preferred or spontaneous rate . For the current study, groups were matched on musical training, so this should not systematically affect our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Musicians are considered a human model of inter-individual differences for studying behavioral-cognitive processes and brain effects of acquiring, practicing, and maintaining specialized motor skills ( Schlaug, 2015 ). Musical training seems to shape certain brain areas through neuroplasticity mechanisms, as neuroimaging techniques have demonstrated differences in structures and functions of the motor regions of musically trained individuals, especially those areas related to auditory and sensorimotor networks ( Gaser and Schlaug, 2003a , b ; Bengtsson et al, 2005 ; Bangert et al, 2006 ; Baumann et al, 2007 ; Hyde et al, 2009 ; Herholz and Zatorre, 2012 ; Steele et al, 2013 ; Zamorano et al, 2017 ), leading to a better motor performance ( Scheurich et al, 2018 ). These differences lead to an enhanced motor function.…”
Section: Introductionmentioning
confidence: 99%